The association between blood MxA mRNA and long-term disease activity in early multiple sclerosis - Coerver, Eline M. E.; Strijbis, Eva M. M.; Petzold, Laura F.; Van Kempen, Zoé L. E.; Jasperse, Bas; Barkhof, Frederik; Oudejans, Cees B. M.; Uitdehaag, Bernard M. J.; Teunissen, Charlotte E.; Killestein, Joep (Frontiers in Neurology, 2022)
Background: Myxovirus resistance protein A (MxA) is a protein that is specifically upregulated by interferon-beta. Homeostatic MxA mRNA levels are potentially correlated with inflammatory disease activity in multiple sclerosis (MS) and could have an important role in MS pathology. Aim: To investigate the association between myxovirus resistance protein A (MxA) mRNA levels in blood and disease activity and progression in MS over a long-term follow-up period. Methods: Baseline blood MxA mRNA levels were determined in a prospective cohort of 116 untreated patients with a clinically isolated syndrome (CIS) or early relapsing remitting MS (RRMS), and related to long-term relapses, radiological disease activity, clinical scores (Expanded Disability Status Scale (EDSS), timed-25-foot walk (T25FW), 9-hole-peg test (9HPT)), MS type, and disease modifying therapy (DMT) use. Results: Low MxA mRNA levels were associated with the occurrence of ≥9 T2-lesions on MRI imaging and the occurrence of relapses during long-term follow-up (median 11 years, IQR 5.91-13.69 years). MxA mRNA levels were not associated with EDSS, T25FW, 9HPT, and MS subtype. Conclusion: Baseline MxA mRNA levels are associated with long-term development of T2-lesions on MRI-scans in our cohort. This confirms the relevance of the endogenous interferon-beta system in the occurrence of MS disease activity.